2021
DOI: 10.3390/insects12100929
|View full text |Cite
|
Sign up to set email alerts
|

Crude Extracts and Alkaloids Derived from Ipomoea-Periglandula Symbiotic Association Cause Mortality of Asian Citrus Psyllid Diaphorina citri Kuwayama (Hemiptera: Psyllidae)

Abstract: Asian citrus psyllid Diaphorina citri Kuwayama (Hemiptera: Psyllidae) is an important economic pest of citrus crops because it vectors the causal pathogen of huanglongbing (HLB; aka citrus greening). Population suppression of D. citri with insecticides has been disproportionally relied on for HLB management and a greater diversity of more sustainable tools is needed. Periglandula spp. is a fungal endosymbiont (family Clavicipitaceae) that forms a mutualistic relationship with members of plants in family Convol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…The analysis of the most effective AK-sF by UPLC/MS/MS indicated the presence of ergot alkaloid compounds (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). Previous findings regarding AK-sF largely agreed with those recently stated [56]. They found that crude extracts derived from different morning glories (Ipomoea sp) related to the Convolvulaceae family as well as some pure ergot alkaloids related to these plants showed strong insecticidal activity against Diaphorina citri adults.…”
Section: Susceptibility Of a Craccivora And B Tabaci To The Probable ...supporting
confidence: 79%
“…The analysis of the most effective AK-sF by UPLC/MS/MS indicated the presence of ergot alkaloid compounds (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). Previous findings regarding AK-sF largely agreed with those recently stated [56]. They found that crude extracts derived from different morning glories (Ipomoea sp) related to the Convolvulaceae family as well as some pure ergot alkaloids related to these plants showed strong insecticidal activity against Diaphorina citri adults.…”
Section: Susceptibility Of a Craccivora And B Tabaci To The Probable ...supporting
confidence: 79%
“…The management of D. citri has played a significant role in HLB dispersal in citrus groves. Eight to twelve insecticide applications are commonly practiced in one cropping season in major citrus-growing countries worldwide [9]. However, the massive and repetitive use of these synthetic insecticides results in environmental pollution and the development of resistance [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Eight to twelve insecticide applications are commonly practiced in one cropping season in major citrus-growing countries worldwide [9]. However, the massive and repetitive use of these synthetic insecticides results in environmental pollution and the development of resistance [9,10]. Therefore, there is a need to develop novel eco-friendly alternatives for managing D. citri.…”
Section: Introductionmentioning
confidence: 99%